2021
DOI: 10.47887/amd.v2i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Miskonsepsi Siswa Dengan Menggunakan Three Tier Multiple Choice Diagnostic Test Pada Materi Gerak Dan Gaya

Abstract: This study aims to identify the level of students’ misconceptions on the concepts of motion and force. The research method used is quantitative descriptive research. Sampling using saturated sampling techniques. The sample in this study consisted of 34 students. This misconception will be identified using diagnostic test. The research instrument used was Three Tier Multiple Choice Diagnostic Test. Based on the result of the study, obtained students who have misconceptions on the concepts of motion and force wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research conducted by previous study explained the identification of misconceptions in the material of electric potential using a three-tier diagnostic test instrument which was carried out using the help of the google form media (Maison et al, 2020;Maryam, 2020). Other research conducted by previous research explains the identification of misconceptions by using a three-tier multiple-choice diagnostic test for movement and style material (Safriana & Irfan, 2021). A study conducted by other study showed the misconceptions that occur in science learning using diagnostic tests to identify students' misconceptions in science (Soeharto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by previous study explained the identification of misconceptions in the material of electric potential using a three-tier diagnostic test instrument which was carried out using the help of the google form media (Maison et al, 2020;Maryam, 2020). Other research conducted by previous research explains the identification of misconceptions by using a three-tier multiple-choice diagnostic test for movement and style material (Safriana & Irfan, 2021). A study conducted by other study showed the misconceptions that occur in science learning using diagnostic tests to identify students' misconceptions in science (Soeharto et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It can also occur because of the students themselves (Didik, L. A. & Bahtiar, 2020;Octavia et al, 2021;Safriana & Irfan, 2021). It can happen due to the need for students' analytical skills.…”
Section: Introductionmentioning
confidence: 99%